2005
DOI: 10.1038/ja.2005.60
|View full text |Cite
|
Sign up to set email alerts
|

Rufuslactone, a New Antifungal Sesquiterpene from the Fruiting Bodies of the Basidiomycete Lactarius rufus

Abstract: A new lactarane sesquiterpene, rufuslactone (1), was isolated from the fruiting bodies of the basidiomycete Lactarius rufus. Rufuslactone (1) is an isomer of a previously described lactarane 3,8-oxa-13-hydroxylactar-6-en-5-oic acid g-lactone (2) from Lactarius necatar. Its structure was elucidated on the basis of spectroscopic data. Rufuslactone (1) showed antifungal properties against plant pathogenic fungi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…We believe that triol 43 is, indeed, a degradation product of 42, owing to the presence of acids during the isolation step, as it will be discussed below in connection with an ester of 43 isolated from Russula pseudodelica. Repraesentins B (48) and C (49) showed a different tricyclic skeleton, consisting of a five-, a six-, and a five-membered ring assembled as in the structure of cerapicol (51), which was isolated from cultures of the ascomycete Ceratocystis piceae [38]. We propose the name cerapicane for the skeleton of 48, 49, and 51.…”
Section: Aristolane and Nardosinane Sesquiterpenesmentioning
confidence: 99%
“…We believe that triol 43 is, indeed, a degradation product of 42, owing to the presence of acids during the isolation step, as it will be discussed below in connection with an ester of 43 isolated from Russula pseudodelica. Repraesentins B (48) and C (49) showed a different tricyclic skeleton, consisting of a five-, a six-, and a five-membered ring assembled as in the structure of cerapicol (51), which was isolated from cultures of the ascomycete Ceratocystis piceae [38]. We propose the name cerapicane for the skeleton of 48, 49, and 51.…”
Section: Aristolane and Nardosinane Sesquiterpenesmentioning
confidence: 99%
“…[5][6][7] China is extraordinarily rich in higher fungi, with over 6000 species reported to belong to about 1200 genera. In our on-going research to explore the biologically active natural products of the higher fungi of China, [8][9][10][11][12] the chemical constituents of the fruiting bodies of Lactarius vellereus were investigated. This report describes the isolation and structure elucidation of an unusual highly functionalized lactarane sesquiterpene, named velleratretraol (1), and its anti-HIV activity.…”
Section: Introductionmentioning
confidence: 99%
“…rufus ( Fig. Compound 11 showed antifungal properties against plant pathogenic fungi [12]. Compound 11 showed antifungal properties against plant pathogenic fungi [12].…”
Section: Figure 13mentioning
confidence: 99%
“…Luo et al [12] reported the isolation of a new lactarane-type sesquiterpenoid, rufuslactone (11) from the fruiting bodies of La. rufus ( Fig.…”
Section: Figure 13mentioning
confidence: 99%